A perspective approach on the amine reactivity and the hydrogen bonds effect on epoxy-amine systems. (15th January 2020) - Mora, Anne-Sophie; Tayouo, Russell; Boutevin, Bernard; David, Ghislain; Caillol, Sylvain
Graphical abstract: Highlights: Hydrogen bonds influence in epoxy-amine systems was reported. The impact of H-bonds on reactivity of amine toward epoxy functions was presented. The influence of H-bonds on advancement of curing reaction was reported. Influence of H-bonds on properties of epoxy materials was summarized. Abstract: The observation and influence of hydrogen bonds in epoxy-system curing and material properties is also discussed through a state of the art of literature. Epoxy-amine systems are widely used polymers for various industrial applications, such as composites, adhesives, paints and coatings due to their high thermal and mechanical properties. The reactivity of epoxy-amine system is crucial for both academic and industrial communities and is dramatically influenced by H bonds. In addition, the ring opening reaction of epoxy system yields hydroxyl groups, which can form hydrogen bonds and thus influence the curing kinetic and the material properties. Those formed hydroxyl groups have also an influence on the properties of cured materials due to their H bond sites. Hence, this article focuses on the description of an amine reactivity scale and on the gathering of literature data mentioning the hydrogen bond observation and study in epoxy-amine system. First, this article presents an amine reactivity scale clarification due to our team expertise and knowledge. Then, all external factors influencing the hydrogen bond formation are described based on several studies. Finally, the influence of hydrogen bond in epoxy-amine system was summarized.